PROPAGASI IN VITRO ANGGREK (Dendrobium phalaenopsis Fitzg) TERHADAP PEMBERIAN HORMON IBA DAN KINETIN - IMAM MAHADI (Jurnal Agroteknologi, 2016)
Orchids are a very popular ornamental plants, but orchids have a very slow vegetative growth, thus requiring special treatment in the grown.To  spur grow than development can be used through tissue culture techniques of multiplication. But the success of the technique of tissue culture is inseparable with give a substance on the plant growth regulator. This study aims to determine the growth  an influence  D.phalaenopsis Fitzg orchids of giving a gaint swith IBA administration and Kinetin according to in vitro  and as well as to obtain a concentration combination of  IBA and Kinetin on the best orchid D.Phalaenops is Fitzg explants.  Base don’t he results of the study indicate that the combination of IBA and Kinetin concentration giving a influence percentage of live explants,   number of shoots and number of roots orchid D. phalaenopsis Fitzg explants.Combination treatment of IBA 1.0 ppm and 0.1ppm Kinetin is a combination of the best treatment to produce a number of shoots orchids.The giving of IBA 0.5ppm in the medium without the addition of kinetin concentration can increase the number of roots of the orchid D.phalaenopsis Fitzg.